STUDENTLERDIŃ LEKSIKALÍQ KOMPETENCIYASÍN FRAZEOLOGIYALÍQ BIRLIKLER ARQALÍ JETILISTIRIW - Jalgasbaeva, G.J. (SCIENCE and SOCIETY, 2025)
The article analyzes scientific ideas aimed at developing the lexical competence of philology students through phraseological units. Methods related to improving students’ lexical competence were also considered.